Estilos de Crianza Parental y la Autonomía Personal en los estudiantes de la Unidad Educativa “Camilo Gallegos Toledo - Sanaguano Espinoza, Pamela Amelia (2024)
This research explored students' attitudes from the "Camilo Gallegos Toledo" Educational Unit towards parental parenting styles and personal autonomy qualities. Both components are essential for adolescents' full development and significantly impact their emotional, social, and academic well-being. Parental parenting affects how young people view themselves and their environment and their ability to face challenges and make conscious decisions. On the other hand, personal autonomy, which involves the ability to manage responsibilities, make independent decisions, and develop one's own identity, is essential for the development of adaptive skills and preparation for adult life. The mixed approach used in this study combines qualitative and quantitative methods, allowing for a full exploration of the phenomena examined. The attitudes and behaviors of students were observed in their natural environment and within a specific time frame through a descriptive and non-experimental design of a cross-sectional type since it facilitated the collection of data at a single moment and provided a representative view of the perceptions and experiences of first, second and third-year students of the Unified General Baccalaureate at the "Camilo Gallegos Toledo" Educational Unit. The research was carried out in collaboration with the participants, who were selected through an intentional and non-probabilistic sample of 155 students distributed equally among the different courses. They voluntarily responded to two validated tools: the PCRI-M Questionnaire, which is intended to assess parents' parenting styles, and a questionnaire adapted to measure personal autonomy qualities. These instruments provided detailed and significant data that allowed a deeper understanding of family and individual dynamics and adolescents' educational and emotional development. This research could serve as a guide for creating educational policies and practices that improve the school environment and the integral development of students.